A humánerőforrás motivációjának vizsgálata Hajdú-Bihar és Szabolcs-Szatmár-Bereg megyékben egy empirikus vizsgálat alapján = Motivation analysis of human resources in Hajdú-Bihar and Szabolcs-Szatmár-Bereg counties based on an empirical research - Ujhelyi Mária (Taylor : gazdálkodás- és szervezéstudományi folyóirat, 2015)
Regional competitiveness is influenced by several factors. Human resources fill in an important position in it. In order to explore the quality of the human capital and its impact on the social and economic cohesion of the Hungarian–Romanian border area, a joint research was conducted by Satu Mare branch of “Vasile Goldiş” Western University of Arad and University of Debrecen, Faculty of Economics and Business Administration. The study “The impact of the human capital quality on the economic and social cohesion in the border area” was implemented in the framework of HU-RO/0901/264/2.2.2 project. In this study questions, related to motivation were analysed from the survey which was filled in by 111 companies from Hajdú-Bihar and Szabolcs-Szatmár-Bereg counties. We surveyed the frequency of the use of 27 motivational tools, their perceived effectiveness, the occurrence of situations which often cause employee dissatisfaction, and the views of respondents about the attitude of employees’ job change. Since the questionnaires were filled in by organizational leaders, their views were analysed in this study. I can conclude that external motivational tools are more frequently used then internal ones. Almost the same items were selected as the most effective and least effective motivation techniques than the most and least frequently used ones. The occurrence of situations which cause employee dissatisfaction is rear. The majority of respondents (64%) believe, that employees rarely think about changing their jobs. Although it is not possible to generalize, the results of this research suggest that the studied organizations are able to retain their employees by using the more traditional external motivational tools.